Coronavirus Disease 2019 (COVID-19) Pandemic - Ni Made Wedri; I Putu Wawan Narendra Putra; I DPG Putra Yasa; IGA Ari Rasdini; I Made Mertha (Nursing and Health Sciences Journal (NHSJ), 2023)
A pandemic that is so sudden and travels so quickly and surely in all parts of the world has an impact on an emergency. A fast, precise, effective, and efficient handling of a pandemic is urgently needed. This literature review aims to present the latest treatments for the Coronavirus Disease 2019 (COVID-19) pandemic based on the results of related studies from 2019-2020. Using 8 databases (Pubmed.gov, Medscape.com, Sciencedrect.com, Google Scholar, Nejm.org, ResearchGate, Garuda Portal, and Thelancet.com) data were searched between 2004 and 2020 in the form of research journals, articles, literature reviews, and handbooks discussing Corona Virus Disease 2019 (COVID-19). Keywords: Coronavirus, Coronavirus disease 2019, COVID-19 to search electronic databases. Journals, articles, literature reviews, and handbooks that are found in accordance with the keywords are then screened and viewed as abstract/full text. Management in the form of basic protection, carrying out surveillance and isolation activities, using personal protective equipment, especially for medical personnel, increasing self-immunity, and controlling comorbid diseases must be carried out to prevent further spread because currently, several antiviral drugs and vaccines are being tested for their effectiveness.